2020
DOI: 10.1002/oby.23014
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Doubles Mortality in Patients Hospitalized for Severe Acute Respiratory Syndrome Coronavirus 2 in Paris Hospitals, France: A Cohort Study on 5,795 Patients

Abstract: Objective: Preliminary data from different cohorts of small sample size or with short follow-up indicate poorer prognosis in people with obesity compared with other patients. This study aims to precisely describe the strength of association between obesity in patients hospitalized with coronavirus disease 2019 (COVID-19) and mortality and to clarify the risk according to usual cardiometabolic risk factors in a large cohort. Methods: This is a prospective cohort study including 5,795 patients aged 18 to 79 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 21 publications
6
71
1
8
Order By: Relevance
“…The current study con rmed older age, 4,7,22−24 obesity, [25][26][27] and prior CVD 4,14 and COPD 4,14 conditions as risk factors for mortality in COVID-19 disease. We observed only weak associations of prior CKD 4,14 with COVID-19 mortality risk.…”
Section: Discussionsupporting
confidence: 66%
“…The current study con rmed older age, 4,7,22−24 obesity, [25][26][27] and prior CVD 4,14 and COPD 4,14 conditions as risk factors for mortality in COVID-19 disease. We observed only weak associations of prior CKD 4,14 with COVID-19 mortality risk.…”
Section: Discussionsupporting
confidence: 66%
“…Similar findings were reported in 5,795 patients with COVID-19, ages 18–79, hospitalized in Paris from February 1 to April 20, 2020, with a mean BMI of 29.3 and 27.2 for women and men, respectively. The odds ratios for relative risk of mortality at 30 days for SARS-CoV-2-infected subjects with a BMI of 25–29.9, 30–35, 35–40, and >40 were 1.41, 1.89, 2.79, and 2.55, respectively, even after correction for age, sex, and co-morbidities ( Czernichow et al., 2020 ). Notably, the relative risk of mortality for people with obesity increased progressively in older individuals.…”
Section: Obesity and Covid-19 Outcomesmentioning
confidence: 99%
“…Selected data on obesity and outcome are shown in Table 1. [17][18][19][20][21][22][23] In western countries, although data from Italy have confirmed earlier Chinese reports, 24 a French study showed that patients with BMI > 35 kg/m 2 were at significantly higher risk for the requirement of intensive mechanical ventilation compared to normal-weight individuals (with BMI lower than 25 kg/m 2 ), even after adjusting for age, diabetes and hypertension. 25 These results were later replicated in a different hospital in France 26 and have generated more interest in the association between adipose tissue excess and disease pathophysiology.…”
Section: Epidemiological Datamentioning
confidence: 78%